Prospective foster parents‘ attitude towards the provided social worker‘s assistance: a case of an X Lithuanian town - Leliūgienė, Irena; Stūglytė-Novickienė, Inga; Kaušylienė, Angelė (Social Welfare: Interdisciplinary Approach, 2017)
The article introduces the significance of social worker’s assistance to prospective foster parents: a case of an X Lithuanian town. The best place for the child development and improvement is the family. For some reasons not all the children are raised in families. Some children have no possibility to live with their biological families, therefore according to the established legislation, they live in foster homes under the supervision of foster parents or are adopted. Children adoption in our country is regulated by different acts of legislation. The activity of the ombudsperson for children’s rights is governed by the Law on the Ombudsman for Children Rights Protection of the Republic of Lithuania (2000), Civil Code of the Republic of Lithuania, Regulations of organization and management of children guardianship (2002), etc. Research aim is to analyze the social service worker’s assistance to the prospective foster parents. The following objectives to reach our goal are presented: to analyze theoretical conception of adoption procedure and enforcement; to discuss the system of the social service workers’ assistance to prospective foster parents; to investigate foster parents’ approach towards the social service worker’s assistance and to reveal the main problems. Research methods: analysis of the scientific literature – scientific analysis of adoption issues. The stages of adoption procedures and the requirements overviewed and analysed are provided; document analysis: documents, acts of legislation, laws and regulations of child adoption regulations are analysed and overviewed; a qualitative study: semi-structured interview, analyzing the foster parents’ approach towards the social service workers’ assistance; problems and probable solutions are identified. The research results are obtained by content analysis. The article presents the following generalizations: 1) adoption is considered as a social process when specific rights and responsibilities are provided to foster parents in order to guarantee the child’s safety. In case of inter-country adoption, the adoption opportunities are estimated, the child is prepared for the adoption and the family for the child is selected. At that period foster parents face internal and external factors. Seeking to grant the children rights and smooth adoption process, professional social workers should coordinate it; 2) institution of the Ombudsman for Children Rights of the Republic of Lithuania and State Child Rights Protection and Adoption Service under the Ministry of Social Security and Labour are also engaged in the adoption and foster care; 3) the research results reveal that the biggest problems for prospective foster parents are extensively long adoption period, lack of social service workers’ assistance and poor knowledge on the available assistance.